Research Advances on Passive Knee Joints Rehabilitation Device - Jiang, Jingang; Gao, Ziwen; Wu, Dianhao; Yu, Xiaoyang; Guo, Yafeng (Recent Patents on Mechanical Engineering, 2022)
Background: After a smooth development of life expectancy per capita and fertility in the nineteenth century, the global population increased in size. Along with the demographic shift in the late nineteenth century, the phenomenon of population aging began to appear in developed countries. A survey from UN reports that by 2050, one in six people worldwide will be over 65 years old (16%), compared to 11 (9%) in 2019. According to another survey, 55% of people over the age of 60 suffer from joint diseases, and the number of people suffering from stroke, arthritis and other knee diseases will also increase accordingly. Objective: An overview of the classification and characteristics of today's knee rehabilitation devices and future developments. Methods: This review discusses the existing knee rehabilitation devices, including various products on the market, patents and some conceptual devices, in the context of the structural characteristics of the knee joint and the rehabilitation requirements of different knee conditions or after knee arthroplasty, and systematically introduces their structural features, differences and the rehabilitation effects achieved. Results: A comparative analysis of three types of passive knee rehabilitation devices according to their use was conducted to summarize the typical characteristics. The problems that exist in today's rehabilitation devices are also analyzed, and their development trends are looked forward to. Conclusion: Knee rehabilitation equipment has a high degree of structural richness, but it does not achieve a good balance of convenience, comfort and functionality, and there should be some room for improvement in the materials, volume of the power source and transmission form of the power system. There will be a good development in the future of knee joint recovery.
Keywords: passive